Is the lack of finger flexor strength an indicator of A2 or A4 pulley injury in Rock climbers? - Iruretagoiena-Urbieta, X.; Rodriguez-López, E. S.; Webster, K. A.; De la Fuente-Ortiz de Zarate, J.; Romero-Pérez, A. G.; Guodemar-Pérez, J. (Journal of Athletic Training, 2019)
Context: A2 and A4 pulley ruptures are the most prevalent rock-climbing related injuries. Flexor digitorum profundus and superficialis strength measurement has been researched in the fields of physiology, performance and post-surgery, but never as a diagnostic tool in pulley injuries. The purpose of this study was to determine whether A2 or A4 pulley pathology causes finger flexor strength decrease and also to establish the relationship between such strength decrease and the tendon-bone distance of A2 or A4 ring finger pulley with diagnostic ultrasound measurements. Methods: A cross-sectional study was conducted in 58 flexor pulleys (A2 or A4) of the 4th digit of rock climbers; half of them were diagnosed pathologic and half were healthy. The tendon-bone distance of A2 or A4 4th digit pulley was measured using diagnostic ultrasound at 21MHz frequency. Additionally, flexor digitorum strength was measured in three types of climbing crimp grips (one finger, open and closed), comparing the pathological finger with the healthy finger. To determine ultrasonographic values, we utilized the most published measurement protocol, which compares the absolute value of tendon-bone distance to the relative value, which is based on comparing the tendon-bone distance of the injured pulley with the sound side. Statistical analysis was conducted using T test, Pearson correlation, and simple linear regression. Results: The fingers diagnosed with pulley pathology had significant strength decreases compared to non-pathological fingers on the one finger crimp (p<0.001), and open crimp (p=0.001) grips. The tendon-bone ultrasonographic distance of the pulley was significantly correlated with one finger crimp strength decrease (r=0.436, p=0.006), while open and close crimp grips were not significantly correlated with ultrasonographic measurements (p>0.05). However, the strength decrease was only correlated with the absolute value and not with the relative one, even if the both type of values correlated between them (r=0.428, p=0.007). Conclusions: Finger flexor digitorum strength is significantly decreased in fingers with A2 and A4 pulley pathology. When evaluating A2 and A4 pulley rupture in rock climbers, finger flexion strength decrease using one finger crimp grip can assist in initial diagnosis, as it was significantly correlated to pulley pathology seen on diagnostic ultrasonography